The intake and digestibility by sheep of oat straw and maize stover offered with different levels of noug (Guizotia abyssinica) meal - Butterworth, M.H.; Mosi, A. (Elsevier, 1986)
An experiment conducted to determine the effect of supplementation with different levels of noug meal on the intake and digestibility in sheep of diets based on maize stover and oat straw. Presents the chemical composition of the three diets.